Bullying in South-East Asian Countries: A review. (July 2015) - Sittichai, Ruthaychonnee; Smith, Peter K.
Abstract: Bullying among young people is a major concern for educators and health professionals. It has been mostly studied in Western countries, but with a significant amount of research in the Asian Pacific Rim countries of Japan, South Korea, Mainland China and Hong Kong, which suggests that it can exhibit different characteristics in other cultural contexts. Research in this area in South-East Asian countries has been relatively neglected, but has begun to appear in recent years. Here, we review studies on bullying in the 10 ASEAN countries. We summarize the nature and main findings of these studies, and comment on similarities and differences with studies in Western and Asian Pacific Rim societies. Finally we make suggestions for future research which will enhance comparability, respecting cultural differences but moving toward a more effective comparative analysis. Highlights: Studies of bullying in ASEAN countries are growing, and are reviewed These studies are making a contribution both locally, and potentially for international comparison Some strengths and limitations of this body of research are considered The possibility of explaining cross-national differences in terms of cultural, linguistic, attitudinal and educational variables is discussed.